A proposed model of corporate income tax compliance behavior in Nigeria: The mediating role of tax compliance cost - Musa, Sulaiman Umar (Kashere Journal of Management Sciences, 2024)
In view of the declining oil prices and production challenges facing Nigeria, which led to high decrease in government revenue, taxation stands to be a sustainable option to ensuring stable flow of revenue for financing development. This paper aims at proposing a model of corporate income tax compliance behavior in Nigeria. The paper reviews previous literature and develops its model based on deterrence and social exchange theories. The paper extends the previous studies by investigating the mediating effect tax compliance cost on the relationship between corporate tax compliance behavior and its determinants (audit and fairness). However, the study has the limitation of being a conceptual model development which has not collected data and analyzed. Hence, future studies can collect data based on the model and analyze to provide recommendations for policy formulation